2007
DOI: 10.1007/s11267-006-9076-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Trends in Surface Water Quality of Five Lakes in Japan

Abstract: Since 1983, the Ministry of the Environment of Japan has conducted nation-wide acid deposition surveys. To investigate the effects of acid deposition on surface water, we used the nonparametric Mann-Kendall test to find temporal trends in pH, alkalinity, and electrical conductivity (EC) in more than 10 years of data collected from five lakes and their catchments (Lake Kuttara: northernmost; Lake Kamakita: near Tokyo; Lake Ijira: central; Lake Banryu: western; and Lake Unagiike: southernmost). The pH of Lake Ij… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Addition ally, the similar surveys conducted by the Ministry of the Environment of Japan (MOEJ) in the Lake Ijira Catchment, Gifu Prefecture, can be referenced. This catch ment showed evidence of the acidification phenomena in soil and inland water (e.g., Yamada et al 2007) suggesting effects of at mospheric deposition. Based on the field data above, standardization of observation methods to obtain good quality data and nu merical modeling of the ecosystem are cur rently being discussed for future monitoring.…”
Section: Catchment Analysis In Different Forest Typesmentioning
confidence: 79%
“…Addition ally, the similar surveys conducted by the Ministry of the Environment of Japan (MOEJ) in the Lake Ijira Catchment, Gifu Prefecture, can be referenced. This catch ment showed evidence of the acidification phenomena in soil and inland water (e.g., Yamada et al 2007) suggesting effects of at mospheric deposition. Based on the field data above, standardization of observation methods to obtain good quality data and nu merical modeling of the ecosystem are cur rently being discussed for future monitoring.…”
Section: Catchment Analysis In Different Forest Typesmentioning
confidence: 79%
“…The high-risk areas in the maps also included some study sites at which surface water has been reported for the past several years. Surface water acidification in Lake Sawanoike (Yoshikawa et al 2000), Lake Yashagaike (MOEJ 2014), and some rivers in the north of Niigata Prefecture (Matsubara et al 2008) was assigned a relative risk category of IV or V. The areas corresponding to category V risk included the Lake Ijira watershed, a site where the effects of acid deposition on the significant water acidification have been reported (Yamada et al 2007;Nakahara et al 2010). Thus, the map of case F may serve as a risk map for surface water acidification.…”
Section: Relative Risk Maps and Their Sensitivities To Different Weightsmentioning
confidence: 99%
“…The seasonal Mann-Kendall test (P \ 0.05) was applied to the 638 observation points in the water quality database for public water bodies (https://www.nies.go.jp/ igreen/). *1 River water in Niigata (Matsubara et al 2008), *2 Lake Yashagaike (MOEJ 2014), *3 surface water in the Leke Ijira watershed (Yamada et al 2007 andNakahara et al 2010), *4 Lake Sawanoike (Yoshikawa et al 2000) …”
Section: *4mentioning
confidence: 99%
“…Wet depositions of hydrogen, sulfur, and nitrogen were among the highest levels observed in a nationwide monitoring program for wet deposition at 53 sites conducted by the Ministry of the Environment of Japan (Yamada et al 2007). The Lake Ijira catchment is located 40 km north-northwest of the Chukyo industrial zone, which has caused some of the most severe air pollution in Japan, and the air pollution emitted from this area is a major source of atmospheric deposition in the catchment (Kitada et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…Kurita and Ueda (2006) found that stream water pH had decreased by 0.3-0.8 units during the last 30 years in some forested catchments on granite and rhyolite bedrocks. Yamada et al (2007) found that the stream water NO 3 -concentration increased from the late 1980s to the early 2000s and that stream water pH began to decrease in the mid-1990s in the Lake Ijira catchment in central Japan.…”
Section: Introductionmentioning
confidence: 99%